2007
DOI: 10.1089/vbz.2006.0652
|View full text |Cite
|
Sign up to set email alerts
|

Synanthropic Flies as Vectors ofCryptosporidiumandGiardiaamong Livestock and Wildlife in a Multispecies Agricultural Complex

Abstract: The capacity of synanthropic flies belonging to the families Calliphoridae, Sarcophagidae, and Muscidae to serve as mechanical vectors of Cryptosporidium and Giardia among livestock and wildlife in a multispecies agricultural complex in northwest Georgia (USA) was studied using fluorescent in situ hybridization (FISH) and immunofluorescent antibody (IFA) techniques. Flies from all three families were carrying viable Cryptosporidium oocysts and Giardia cysts internally and externally, and deposited them on trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 30 publications
1
43
0
3
Order By: Relevance
“…Outro aspecto observado nas visitas semanais foi a presença eventual de animais adultos no local das casinhas com consequente eliminação de fezes contaminando a pastagem, provável fonte de infecção para as bezerras. Adicionalmente, moscas, comumente presentes no ambiente das casinhas, são vetores mecânicos de oocistos de Cryptosporidium e cistos de Giardia (CONN et al, 2007).…”
Section: -------Intervalo De Confiança _______ Risco Relativo Ajustadounclassified
See 1 more Smart Citation
“…Outro aspecto observado nas visitas semanais foi a presença eventual de animais adultos no local das casinhas com consequente eliminação de fezes contaminando a pastagem, provável fonte de infecção para as bezerras. Adicionalmente, moscas, comumente presentes no ambiente das casinhas, são vetores mecânicos de oocistos de Cryptosporidium e cistos de Giardia (CONN et al, 2007).…”
Section: -------Intervalo De Confiança _______ Risco Relativo Ajustadounclassified
“…Mas, o risco de infecção diminui significativamente com o aumento da idade do animal (MALDONADO-CAMARGO et al, 1998;SCHAAF, 1999). Além disso, animais jovens são mais sensíveis à infecção clínica por espécies do gênero Eimeria, que estão envolvidas em perdas econômicas, por causarem diarreia (CORNELISSEN et al, 1995;MATJILA;PENZHORN, 2002). A ocorrência das espécies de Eimeria varia de acordo com a idade dos animais hospedeiros (MENEZES;LOPES, 1995).…”
Section: Introductionunclassified
“…Synanthropic flies have been shown to mechanically transport Cryptosporidium oocysts (10). In a recent study, Conn and collaborators showed that dung beetles can potentially disseminate Cryptosporidium oocysts (11).…”
Section: Genotyping and Molecular Epidemiologymentioning
confidence: 99%
“…Synanthropic flies have been shown to mechanically transport Cryptosporidium oocysts (10). In a recent study, Conn and collaborators showed that dung beetles can potentially disseminate Cryptosporidium oocysts (11). Sixteen dung beetles of the genera Onthophagus, Ataenius, and Aphodius were collected from facilities and pastures housing domestic sheep, dairy cattle, beef cattle, and horses as well as fields frequented by Canada geese and white-tailed deer.…”
Section: Genotyping and Molecular Epidemiologymentioning
confidence: 99%
“…Diversas familias de dípteros braquíceros como Muscidae, Fanniidae, Calliphoridae o Sarcophagidae, presentan especies con demostrado papel en la difusión de virus, bacterias y protozoos enteropatógenos [25][26][27][28] .…”
Section: Artrópodos Y Saludunclassified